2011
DOI: 10.12660/rbfin.v9n2.2011.2825
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes do Sucesso dos Investimentos de Private Equity e Venture Capital no Brasil

Abstract: This paper investigates the determinants of performance of the investments of private equity and venture capital (PEVC) funds in Brazil. We use two unique databases: the First Brazilian Private Equity and Venture Capital Census and the Guia-GVcepe Endeavor, with information on this industry for the period 1999 to 2007. As measures of performance we use the percentage and number of exits throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In terms of research on the relationship between investor experience and investment returns of venture capital funds. Siqueira and Carvalho (2011) [6] studied the influencing factors of the investment return of venture capital funds, and believed that the investment return of venture capital funds depends on the fund size, investment experience, etc., and believed that investment experience and investment return are positively correlated. Zarutskie (2010) [7] examined the relationship between the human capital of the management team of venture capital funds and the return on investment, and found that the richer the investment or entrepreneurial experience of the management team, the greater the proportion of successful exits in the portfolio.…”
Section: Research On Investor Experience and Investment Return Of Venture Capital Fundmentioning
confidence: 99%
“…In terms of research on the relationship between investor experience and investment returns of venture capital funds. Siqueira and Carvalho (2011) [6] studied the influencing factors of the investment return of venture capital funds, and believed that the investment return of venture capital funds depends on the fund size, investment experience, etc., and believed that investment experience and investment return are positively correlated. Zarutskie (2010) [7] examined the relationship between the human capital of the management team of venture capital funds and the return on investment, and found that the richer the investment or entrepreneurial experience of the management team, the greater the proportion of successful exits in the portfolio.…”
Section: Research On Investor Experience and Investment Return Of Venture Capital Fundmentioning
confidence: 99%
“…In Brazil, Siqueira, Carvalho and Netto (2011) investigate the determinants of the success of PE/VC investments, using data from the period from 1999 to 2007. The authors emphasize that the factors influencing the performance of investment vehicles are: volume of capital committed, number of investments made, existence of co-investments, foreign origin and experience of the management organization, focus on private equity firms, intensity of contact between managers and portfolio companies and the number of seats on boards of directors of companies invested by fund manager.…”
Section: Literature Review and Hypotheses Develop-mentmentioning
confidence: 99%
“…Information about fund performance provided by GPs, if it exists, may have reporting bias. Siqueira et al [2011] investigated the determinants of fund performance at the deal level using census information, but in the absence of return information, they use exits through IPO or trade sale as a proxy for success.…”
Section: Evolution Of Fundraising In Latin Americamentioning
confidence: 99%